Keanekaragaman Jenis Kantor Semar (Nephentes Spp.) Di Padang Padeha Taman Nasional Lore Lindu - Julianto, Eki Dwi; Mallombasang, Sri Ningsih; Labiro, Elhayat (Universitas Tadulako, 2021)
The research was conducted in the Padang Padeha Region, North Lore District, Poso Regency, Central Sulawesi Province. The Padang Padeha area is included in the work area of the Lore Lindu National Park Center. This research was conducted from April to May 2017. The purpose of this study was to determine the diversity of pitcher plants (Nepenthes spp) in Padang Padeha, Lore Lindu National Park. This study uses the line transect method and the identification process of semar bag (Nepenthes spp) can be carried out in the field by paying attention to the morphological form. As well as determining the plots to be carried out as many as 10 plots. From the results of observations, there are 3 types of pitcher plants whose names have been identified, and based on the highest number of species, Nepenthes Spp. namely: Nepenthes Tentaculata as many as 120 individuals and the lowest number of species is owned by Nepenthes Mirabilis as many as 30 individuals and Nepenthes Maxima as many as 95 individuals. Where as a whole is spread in the Padang Padeha area.Kata Kunci: Keanekaragaman Jenis, (Nepenthes Spp.), Taman Nasional Lore Lindu